Effect the Coefficient of Performance in the Production of Architecture (Journal of University of Babylon for Engineering Sciences, 2018)
If the procedural definition of the performance act is ("the mixing of subjective and objective effort in a logical and conscious action to reflect the architectural thought and create the optimal expression between the desired image and the possible image with references from inside or outside the architecture to meet the need of the receiver and thus accept).Is this dimension performative specific performance coefficient can be measured by the performance of architecture through which, if we know that the definition of coefficient of performance ((is the energy required relative to the paid energy)) and the relationship of these two definitions, an architectural concept of performance evaluation, which is a system that helps in measuring and evaluating the relationship between the efficiency of the performance duties and functions of the job Eshetglha and all of the behavior and the ability of the product on the best results achieved performance according to the level of performance and the degree of actual achievement, which helps to know the strengths and weaknesses of the past performance and determine how to avoid weaknesses and investment strengths at the present time and in the pain Will be accepted to reach the highest degree of performance efficiency, including the individual and the community. If the objective of architecture core is the benefit of man all the physical, moral, social and economic levels ... etc., since this science dimension Adaiaa goal of the benefit of man and therefore society finds research his problem through the questions, you can find a constant coefficient of performance architecture can be measured? How to take advantage of the performance coefficient can be used as a criterion for measuring the benefit of architecture, and what is the relationship between the benefit of the production and function of the architecture, what specializes performance output coefficient or usefulness of the function of architectural production. This gives the signal to determine the main hypothesis that architecture science goal is to find the function of the product of working on the benefit of the human system and this system consists of a set of elements and through the study of these elements and their relationships can be reached Adaiatha plants. Whereas the secondary hypothesis: the possibility of finding for the benefit of architectural output function for performing access to read in the life of architecture through the elements of its projects components and can therefore be life indicator architectural output and ensure the preservation of Adaiatha.In this case, it is possible to refer the information base to the search through the variable used in the coefficient of performance of the architectural output symbolized by the symbol X and the theoretical objectives of the research in the possibility of knowing, containing and directing the change in the nature of the performance awareness of the benefit of a particular architectural product by knowing its practical function in providing a method of measurement Which enables them to identify a new relationship and a new life in architecture that depends mainly on the performance factor of the architectural output and its relation to elements of the architectural system to reach a building that is full of life and as long as possible. Independent variables: the components of the performance of the architectural production of energy production, required and paid and its impact on the life of architecture. The research was based on a methodology that consisted of the following axes: the axis of the efficiency of performance, the role of the mind and its transfer to its own, and the focus of the study examples and conclusions and recommendations.